Геродот як предтеча географічного українознавства - Влах, М. (Історико-географічні дослідження в Україні, 2019)
Розкрито актуальність україноцентричного дослідження писемних пам’яток
давньогрецької культури для історико-географічного обґрунтування етногенезу
українців, витоків української державності, європейського цивілізаційного вибору
України. На підставі аналізу тексту праці “Історії…” давньогрецького філософа
Геродота (480–425 рр. до Р. Х.) у рамках описово-країнознавчої парадигми проаналізовано перший комплексний географічний опис Скіфії-України. Висвітлено
покомпонентний опис природи, а також людності у політико-географічному, демогеографічному, етногенетичному, етногеографічному контекстах. Зроблено висновок, що Геродот є предтечею географічного українознавства – трансдисциплінарного наукового напрямку, що вивчає природу, населення та господарство території формування і сучасного розміщення української етнополітичної спільноти. The relevance of the Ukrainian-centric research of written cultural monuments of
ancient Greek culture for the historical and geographical justification of ethnogenesis
of Ukrainians, origins of Ukrainian statehood, European civilization choice of Ukraine is
revealed. On the basis of the analysis of the text of the work «History ...» of the ancient
Greek philosopher Herodotus (480-425 years BC.) In the framework of the descriptiveethnographic
paradigm the first comprehensive geographical description of Scythia
Ukraine, the territory extending from the Istr (Danube) to the west, was analyzed. to Tanais
(Don) in the east, from the Black Sea in the south to Polissya in the north. The component
description of nature (water supply system, relief, soils, climate, vegetation), as well as
population in political-geographical, demogeographic, ethnogenetic, ethnogeographical
contexts is highlighted. The territorial community, formed by the Black Sea-Azov basin’s
hydropower system, the continuity of the cultural process on the Ukrainian lands from
ancient times is evidenced by the ancientness of Ukrainians, the autochthonous roots
of their ethnogenesis from the time of the Trypillian and Scythian ages. The unity of the
chorological and historical approaches, anthropocentrism (the type of worldview, in which
the center of scientific knowledge is man and the Earth as the place of its existence) are
characteristic features of Herodotus’ country-descriptive description of Scythia-Ukraine.
It is concluded that Herodotus is the forerunner of geographic Ukrainian studies – a
transdisciplinary scientific direction that studies the nature, population and economy of
the territory of the formation and modernization of the Ukrainian ethnopolitical community.
It is emphasized that the geographical isolation of Scythia from the rest of the wellknown
ancient Greeks of Oikumeni is an important source of spatial history, historical
geography of Ukraine, history of geography of Ukraine. The geospatial delineation of
Europe and Asia along the Don river basin, which today became the military Ukrainian
frontier, is relevant. It is revealed that the problems of the Ukrainian-Russian inter-state
have deep historical roots due to the cancellations of settled (agricultural) and nomadic
ways of life, the western democratic and eastern despotic regime.